2015
DOI: 10.1210/jc.2014-3649
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Fluid Concentrations of Lipids and Their Metabolites Are Associated With Intraovarian Gonadotropin-Stimulated Androgen Production in Women Undergoing In Vitro Fertilization

Abstract: These results suggest that ovarian androgen production is related to intraovarian exposure to lipids, independently of inflammation and mainly through ineffective NEFA β-oxidation (as shown by higher acylcarnitine levels). Inflammation is also associated with intraovarian androgenesis, independently of lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…As a prevalent endocrine disease, polycystic ovary syndrome (PCOS) usually manifests as menstrual malfunction and hyperandrogenism (HA) in women in puberty . In PCOS, androgen generation by the ovaries is disturbed, and increased generation of testosterone occurs, compared to estrogen . In women, androgen generation occurs in the adrenal glands as well as ovaries.…”
mentioning
confidence: 99%
“…As a prevalent endocrine disease, polycystic ovary syndrome (PCOS) usually manifests as menstrual malfunction and hyperandrogenism (HA) in women in puberty . In PCOS, androgen generation by the ovaries is disturbed, and increased generation of testosterone occurs, compared to estrogen . In women, androgen generation occurs in the adrenal glands as well as ovaries.…”
mentioning
confidence: 99%
“…In this study, we also found that the inflammation was associated with androgen production as well, although to a lesser extent (reflected by IL-6) [ 77 ]. As for NEFA metabolites, the inflammation marker TNF- α is known to serine-phosphorylate IRS-1 [ 78 ], thus contributing to insulin resistance.…”
Section: Role Of Lipotoxicity and Insulin Action In The Developmenmentioning
confidence: 79%
“…Thus, we demonstrated that lipotoxicity can directly trigger androgen overproduction in vitro , with inhibition of the MEK/ERK pathway as a potential mechanism. Furthermore, using follicular fluid as a surrogate of the intraovarian milieu, we showed that local gonadotropin-induced androgen production is associated with intraovarian exposure to lipids and that this association may be mediated by ineffective NEFA β -oxidation ( Figure 1 , bottom left part) [ 77 ].…”
Section: Role Of Lipotoxicity and Insulin Action In The Developmenmentioning
confidence: 99%
“…Analyzing the networks obtained we noticed the involvement of many pathways related to lipid metabolism in FF and it is known from the literature that an intravenous infusion of lipids induces the production of androgens at the follicle level (Mai et al, 2008). Gervais, Battista, Carranza‐Mamane, Lavoie, and Baillargeon (2015) suggest that the local production of androgens is associated with the presence of intraovarian lipids and that this association can lead to inflammatory phenomena implicated in intraovarian androgenesis, which, for example, characterizes women with PCOS. In our previous study, we reported in FF high levels of steroid precursors of mineralocorticoid hormones in comparison to serum and these can be involved in the ovarian renin‐angiotensin system that influences the development of the follicle.…”
Section: Discussionmentioning
confidence: 99%